Factors Affecting Regional Financial Independence In Regency/City Governments In North Sumatera (2015-2019 Period) - Elsi Nonni Theresia Siregar (TRIGIN PUBLISHER, 2020)
The purpose of this research is to examine the effect of economic growth, local revenue, capital expenditure, general allocation of funds and regional investment toward regional financial independence in regency/city at North Sumatra for the 2015-2019 period. The sampling technique used in this study was purposive sampling method with a total sample size of 12 and a total of 60 observations. The data used in this study were secondary data. The research data was obtained from the website of the North Sumatra Central Bureau of Statistics and the Directorate General of Fiscal Balance. The results show that partially the economic growth and local revenue have a positive effect on regional financial independence, general allocation funds have a negative effect on regional financial independence, capital expenditure and regional investment have no effect on regional financial independence. Meanwhile, simultaneously economic growth, local revenue, capital expenditure, general allocation of funds and regional investment have a positive and significant effect on regional financial independence.